Non-Pharmacological Approach of Food & Yoga to Mollify Tension Type-Headache Induced by Stress Incited Dharan of Kshudha Vega (Suppression Of Urge Of Hunger) - Raj, Pooja; Bhati, Kirti R; Patwardhan, Ravindra P (International Research Journal of Ayurveda & Yoga, 2022)
Disorders caused by men’s imprudence and indulgence in unhealthy lifestyles lead to the development of lifestyle disorders. Suppression of natural urge of hunger is commonest & frequent health perilous. Objective: To investigate the role of Bhramari Pranayam in the prevention of tension type headaches, as well as to provide facts on the necessity of eating timely. Material & Methods: The study was a prospective, parallel, randomized controlled trial. After approval from Institutional Ethical Committee, Clinical Trials Registry (India), 30 participants with the onset of headache in the past just before mealtime & ≥ 3 months were enrolled for study after determining the inclusion criteria & taking consent from the outpatient-inpatient department of the concerned institute and were divided into two groups. Group A participants were counseled for only timely consumption of food & Group B participants were counseled for timely consumption of food along with Bhramari Pranayam for 45 days. All patients were asked to maintain a headache diary. Observation and Result: The results of the treatment were assessed based on relief in signs and symptoms of the assessment criteria. The mean age interval was 30-40 years. Stress was a common factor in all participants, skipping morning meal habits were common in 53.33% of males,66.67% of females.48%participants had an irregular sleeping pattern.96.67% showed gradual onset of tension headache, tight quality 46.66% & temporal-frontal as the commonest site of pain in 36.67%. Conclusion: Bhramari Pranayam along with timely consumption of food showed a better effect.